Community-Based State Forest Management (social forestry) In Purworejo Regency Of Central Java Indonesia - Dwijanti, Ratna; Sutrisno, Joko; Pujiasmanto, Bambang; Rahayu, Endang Siti (Advances in Social Sciences Research Journal, 2018)
The study was conducted in Purworejo Regency, Central Java Province, with the aim to know the factors influencing the state forest management by community approach. The analysis unit is the community that manages the forest together in the institution of Community Joint Forest Management (PHBM) which is determined as the research objective. Purworejo Regency is located in Purworejo Forest Management Unit (KPH). Repressive approach towards the society around the forest caused society’s reaction to the area, disruption to the forestry crops are frequent, and deforestation becomes evidence of dissonance between society and the manager of forest area in Bogowonto River Flow Territory. In the region there are 261 villages in Purworejo Regency, 168 among them are located in Bogowonto DAS, and are managed by 269 forestry farmer groups. Participant farmers’ participation with score of 70.33 (71.04%) and community’s participation in PHBM of 0.831 are categorized in very strong closeness level. From the significance test (t-test) is obtained tcount = 12.232 is higher than t0.05 = 2.000 at the significance level of 5% meaning the relationship between education and participation in forest management. The farmers’ income from the PHBM activity earned from the output sharing of forestry products is ranging from Rp. 450,000 – Rp. 12,400,000, with the average is amounted to Rp. 6,370,290 per year. From the research result is found that the PHBM participant farmers have income amounted to Rp. 450,000 - Rp. 4,433,333 with total is 11 people (15.94%), the income Rp. 4,433,334 – Rp. 8,416,667 with total is 43 people (62.32%) and those who have income amounted to Rp. 8,416,668 - Rp. 12,400,000 with total is 15 people (21.74%).